Measuring magnetic fields in laser-driven coils with dual-axis proton deflectometry. (1st July 2021) - Bradford, P; Dearling, A; Ehret, M; Antonelli, L; Booth, N; Carroll, D C; Clarke, R J; Glize, K; Heathcote, R; Khan, M; Moody, J D; Pikuz, S; et al.
Abstract: By driving hot electrons between two metal plates connected by a wire loop, high power lasers can generate multi-tesla, quasi-static magnetic fields in miniature coil targets. Many experiments involving laser-coil targets rely on proton deflectometry directed perpendicular to the coil axis to extract a measurement of the magnetic field. In this paper, we show that quantitative measurements using perpendicular probing are complicated by the presence of GV m −1 electric fields in the target that develop on sub-ns timescales. Probing parallel to the coil axis with fiducial grids is shown to reliably separate the electric and magnetic field measurements, giving current estimates of I  ≍ 5 kA in 1 mm- and 2 mm-diameter wire loops. An analytic model of proton deflection in electric and magnetic fields is used to benchmark results from the particle-in-cell code and help deconvolve the magnetic and electric field deflections. Results are used to motivate a new experimental scheme that combines a single-plate target with axial proton probing and direct current measurements. This scheme has several important advantages over the traditional target and diagnostic set-up, enabling the robust measurement of coil magnetic fields and plasma properties, as well as making it easier to validate different theoretical models at a range of laser intensities.